Audiometric Evaluation of Hearing Loss– A Study of 100 Cases - Asaduzzaman, AKM; Rabbani, Sarder Mohammad Golam; Islam, Md Tauhidul; Hossain, Mohammod Delwar; Alam, Shafiul; Azad, Muhammad Ali (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Audiometry is the measurement of hearing acuity. If it is done by using pure tones then it is called pure tone audiometry. It is the most commonly used method for hearing measurement. Objective: To find out the type and degree of hearing loss. Materials and Methods: The cross sectional prospective study was carried out in the Audiology unit of the Department of Otolaryngology-Head and Neck Surgery, Combined Military Hospital (CMH), Dhaka, in a period of 06 months from o1.03.2016 to 31.08.2016 among those complaining hearing loss attending in this hospital. 100 cases of hearing impaired people were taken and the data were collected by interviewing the cases as per questionnaire from history, examinations and investigation reports. Results: This study revealed that people of 21-30 years were most common sufferer of hearing loss and female was predominant (61%). The most common type of hearing loss was conductive type. In the right ear type of deafness were 46 cases (51.11%) of conductive type of deafness, 20 cases (23%) of mixed type of deafness and 17 cases (18.88%) of sensorineural type of deafness. In the left ear it was 53 cases (61.62%) of conductive type of deafness, 20 cases (23.25%) of mixed type of deafness and 13 cases (15.13%) of sensorineural type of deafness. This study showed that other ranks (ORs) families (45%) were commonest group of people. This study also revealed that Chronic suppurative otitis media (CSOM) (39%) was the commonest cause of hearing loss. Conclusion: This study denoted that commonest type of hearing loss was conductive type, commonest degree of hearing loss was mild degree and commonest causes of hearing losses were CSOM and otitis media with effusion (OME). Since, these conditions are preventable. So, appropriate measures can prevent hearing impairment in this study group. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 30-34